Problems of the Activity of Lawyers in Protection in Criminal Cases in Respect of Victims of Domestic Violence - Z. M. Beryoza (Теоретическая и прикладная юриспруденция)
The article is devoted to the problems that arise in the activities of lawyers in providing legal assistance to victims of domestic violence who were charged with causing harm to the life and health of their offenders. Self-defense (necessary defense) is considered as the main defense strategy in such criminal cases. The author compares legislative approaches and features of law enforcement practice that arise when using this strategy on domestic and foreign experience (using the example of the United States), dwelling separately on cases where self-defense took place outside an open conﬂict (in non-confrontational circumstances). Based on the analysis of approaches to this problem in foreign jurisdictions, the author proposes in Russian practice to use evidence conﬁrming the history of domestic violence and the psychological trauma they cause in the victim in such categories of cases in order to conﬁrm the compliance of the behavior of the victim of violence with the criteria for necessary defense.